2001
DOI: 10.1034/j.1600-0668.2001.011001010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renovating an Office Building on Occupants’ Comfort and Health

Abstract: An intervention study was performed in a mechanically ventilated office building in which there were severe indoor climate complaints among the occupants. In one part of the building a new heating and ventilation strategy was implemented by renovating the HVAC system, and a carpet was replaced with a low-emitting vinyl floor material; the other part of the building was kept unchanged, serving as a control. A comprehensive indoor climate investigation was performed before and after the intervention. Over a 2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 1 publication
1
23
1
Order By: Relevance
“…The chamber was thoroughly cleaned prior to the experiments and 'baked' for one week at a temperature of 40°C to reduce any residual pollution on the inner surfaces of the chamber and its ducting. No chemical measurements were performed prior to the experiment to examine whether the background pollution level was in fact low, but many previous experiments performed in the same chamber have documented that the chamber is indeed low-emitting (e.g., Fang et al, 1998a,b;Kjaergaard et al, 1999;Pejtersen et al, 2001;Zhang et al, 2016b). The sensory assessments of air quality made by the subjects in the present experiment (see the Results section and Fig.…”
Section: Facilitiesmentioning
confidence: 99%
“…The chamber was thoroughly cleaned prior to the experiments and 'baked' for one week at a temperature of 40°C to reduce any residual pollution on the inner surfaces of the chamber and its ducting. No chemical measurements were performed prior to the experiment to examine whether the background pollution level was in fact low, but many previous experiments performed in the same chamber have documented that the chamber is indeed low-emitting (e.g., Fang et al, 1998a,b;Kjaergaard et al, 1999;Pejtersen et al, 2001;Zhang et al, 2016b). The sensory assessments of air quality made by the subjects in the present experiment (see the Results section and Fig.…”
Section: Facilitiesmentioning
confidence: 99%
“…Sensory pollution loads were also reduced when felt carpet was substituted with low‐polluting polyolefine in another building (Wargocki & Fanger, 1997). There are many other examples of that kind (Wargocki et al., 1999; Pejtersen et al., 2001; Wargocki et al., 2002a; Bakó‐Biró et al., 2004).…”
Section: Reduction Of Sensory Pollution Loads In Buildingsmentioning
confidence: 99%
“…The same pollution source was introduced or removed from two normal office spaces, one in Denmark (Wargocki et al ., 1999) and one in Sweden (Lagercrantz et al ., 2000), in order to modify the pollution load. The source was a tufted bouclé carpet with 100% polyamide fibers and latex backing of the type that is quite common in existing buildings; it was taken from an office building with a history of SBS symptoms (Pejtersen et al ., 2001), where it had been in use for 20 years. Air temperature, relative humidity, noise level, air velocity, and outdoor air supply rate remained unchanged, and were not affected by the intervention (Table 1); the air was well mixed.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…A number of studies have shown that reducing the pollution load on indoor air by removing sources of pollution decreases the number of people dissatisfied with the air quality (van Beuningen et al ., 1994; Wargocki & Fanger, 1997) and the prevalence of sick building syndrome (SBS) symptoms (Norbäck & Torgén, 1989; Pejtersen et al ., 2001). In addition to the effects mentioned above, recent Danish experiments have shown that decreasing the pollution load improves the performance of simulated office work (Wargocki et al ., 1999).…”
mentioning
confidence: 99%